The role of the cholecystokinin 2 receptor in cancer - Mayne, Cerys Mary (2011)
The gastrointestinal (GI) hormone, gastrin, promotes cancer progression and its down-regulation has been linked to reduced cancer stem cell numbers. Gastrin acts through the cholecystokinin-2 receptor (CCK-2R) and its biological effects are blocked by CCK-2R inhibitors. We investigated the regulation of the CCK-2R and its potential role in promoting survival of cancer stem cells (CSC).